The scope of the most important duties of the employee in the light of provisions of the Labour Code - MAJCHRZAK, KATARZYNA (Prawo Kanoniczne, 2017)
The scope of major employee’s duties is governed by Art. 100 of the Labour Code. ese, however, are not all employee’s responsibilities towards his or her employer, but only the most common. e primary responsibility of each employee is a careful and conscientious performance of work and compliance with ocial instructions. Give the above, instructions must be strictly job-related and consistent with the law or the employment contract. A sample catalogue of employee’s duties can be found in Art. 100 §2 of the Labour Code. It includes, for example, the duty to care for the welfare of the employment establishment and to maintain condentiality of information, the disclosure of which could harm the employer. An important duty of each employee is also to follow the principles of social coexistence. A violation of this duty, such as use of physical force against other employees may even lead to termination of the employment contract without notice due to the employee’s fault, in accordance with Art. 52 of the Labour Code.